1997
DOI: 10.3168/jds.s0022-0302(97)76200-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hull-less Barley, Barley, or Corn for Lactating Cows: Effects on Extent of Digestion and Milk Production

Abstract: Six lactating, cannulated Holstein cows were used in a double 3 x 3 Latin square design to compare the effects of hull-less barley with barley and corn on ruminal fermentation, rate of passage, flow of nutrients to the duodenum, and milk production. Diets consisted of 60% concentrate, 30% barley silage, and 10% alfalfa hay (dry matter basis). Concentrates contained steam-rolled grains: hull-less barley, barley, or corn. Dry matter intake was unaffected by grain source, but starch intake tended to be greatest w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
1
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 27 publications
11
48
1
3
Order By: Relevance
“…In contrast to our findings, Khalili et al (2001) reported an increase in milk protein and lactose yield in combination with increased MY when replacing dietary barley with maize. In this work, the milk composition was not altered by the starch source; this finding is consistent with the results of other researchers (DePeters and Taylor, 1985;McCarthy et al, 1989;Yang et al, 1997;Silveira et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast to our findings, Khalili et al (2001) reported an increase in milk protein and lactose yield in combination with increased MY when replacing dietary barley with maize. In this work, the milk composition was not altered by the starch source; this finding is consistent with the results of other researchers (DePeters and Taylor, 1985;McCarthy et al, 1989;Yang et al, 1997;Silveira et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…In some cases, maize supplements have been found to increase MY relative to that observed with barley (McCarthy et al, 1989;Overton et al, 1995;Khalili et al, 2001); however, this effect is not always observed (DePeters and Taylor, 1985;Grings et al, 1992;Yang et al, 1997). In our experiment, the yield of milk constituents was also not affected by the type of the concentrate starch, probably because of the absence of differences in MY.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In general, fermentation of structural carbohydrates yields greater amounts of acetic acid and lower amounts of propionic acid compared with the fermentation of starch, which yield greater amounts of propionic acid. The greater rates of starch degradation for BBD compared with CBD led to greater propionate concentrations in the former and greater acetate concentrations for the latter consistent with the findings of previous studies (McCarthy et al, 1989;Casper et al, 1990;Yang et al, 1997;Khorasani et al, 2001). Greater concentrations of acetate for rolling than for grinding and greater concentrations of propionate for grinding than for rolling could be attributed to the inverse relationship between acetate and propionate, which reflect the relative proportions of cellulolytic and amylolytic bacteria in the rumen (Knowlton et al, 1996;Dehority and Orpin, 2003).…”
Section: Rumen Fermentationsupporting
confidence: 87%
“…YANG et al (1997). A produção de leite apresentou uma média geral de 26,95 ±0,12 kg/dia, decrescendo linearmente (P<0,05) com o aumento do nível de cevada na dieta (TABELA 4).…”
Section: Methodsunclassified